MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD ISLAM AZ ZAHRA BANDAR LAMPUNG - Mega Ria Pusvita; Subandi Subandi; Meriyati Meriyati (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of human resource management in improving educational quality at SD Islam Az Zahra Bandar Lampung. A qualitative field research approach was employed. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings indicate that human resource management has been implemented through four main functions: planning, organizing, actuating, and controlling and evaluating. Planning includes human resource needs analysis and competency development. Organizing is carried out through appropriate task distribution and effective coordination. Actuating is implemented through teacher training, professional development, supervision, and motivation. Controlling and evaluating are conducted through regular performance monitoring and follow-up actions. The implementation of these management functions contributes to improving teacher professionalism, learning effectiveness, and the overall quality of education at SD Islam Az Zahra Bandar Lampung.